Versos para os pequeninos, de João Köpke: um tesouro literário pouco explorado - Farias, Morgana de Medeiros (2022)
The main objective of this thesis is to analyze the manuscript Versos para os pequeninos, written by João Köpke, from Rio de Janeiro, which dates back to the 19th century, but does not have a defined date of creation. The analyzes are based on investigations about the author's creative competence, the artistic aspects of his production, noting his inclination to deal more with playful subjects than with pedagogical ones, a fact that highlights him among other poetry authors of the time. The composition we are dealing with is a compilation of children's poems from which we have chosen four of them as corpus, entitled “O balanço", "O ato ilis", "Meu cavallo" and "Conversas", these that deal with a very perceptible children's perspective, dealing with themes common to the child's universe. We understand that there was a suppression in the author's biographical path, in the sense that it was not clear that he wrote texts of this nature. Some of his faces were shown in previous researches, but another was practically omitted: that of a writer of children's literature, which we will see up close, has aesthetic and semantic value. To reach our objective, we mobilized theories and academic knowledge about the relationship between literature and education in the 19th century, looking at the school space and the prevailing ideologies, reaching the origins of children's literature and research around Köpke, counting, for that , with authors such as Salem (1970), Carvalho (1985), Hilsdorf (2005), Panizzolo (2006), Lajolo and Zilberman (2007), Coelho (2010) and Arroyo (2011), Santos (2013), Mortatti (2015) , and Ferreira (2015). In a second moment, we stop to study the author's biographical path more closely, aiming to understand a little of his trajectory, his inclination to education, as well as knowing some of the works he wrote in the interface of this area with literature. Studies such as those by Hilsdorf (1988), Chicoski (2010), Matta (2011), Panizzolo (2011), Santos (2013), Belo (2014), Mortatti (2015) and Ferreira (2018) contributed to the assembly of this remarkable trajectory. , which caught our attention at first glance. Finally, we mobilize theories about the poetic text, to understand its particularities and, having done that, we enter into comparisons between poems that Köpke created, to compose the manuscript, with those of three other authors of his time, and only then we close the work. with the analysis of the cited corpus. Bosi (1977), Held (1980), Lajolo (1982), Bordini (1991) and Ferreira (2017) directly contributed to the reasoning of this section. For us, in the case of the manuscript, João Köpke's intention is visible in writing texts through which children feel represented, where their experiences are present, without fixed teachings. Therefore, with this research, we redimension the place of this author in studies on literature, resignifying his name and providing means of questioning the erasure that occurs in relation to him in the national literary historiography.